2015
DOI: 10.3109/0886022x.2015.1012984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silymarin on methotrexate-induced nephrotoxicity in rats

Abstract: Methotrexate (MTX) is widely used in the treatment of various malignancies and nononcological diseases but its use has been limited by its nephrotoxicity. Silymarin (SLY), a natural flavonoid, has been reported to have antioxidant, anti-inflammatory and anti-apoptotic effects. This study was carried out to determine whether SLY exerts a protective effect against MTX-induced nephrotoxicity. Rats were divided into six groups: Group 1 (saline, i.p., single injection), Group 2 (0.5% carboxymethyl cellulose (CMC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
6
25
0
Order By: Relevance
“…Additionally, apoptosis was increased. Silymarin treatment led to significant histopathologic improvements in the kidney sections (44). The literature therefore supports our study's finding that silymarin is nephroprotective.…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, apoptosis was increased. Silymarin treatment led to significant histopathologic improvements in the kidney sections (44). The literature therefore supports our study's finding that silymarin is nephroprotective.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of present study are also similar with those reported by Dabak DO et al [17] which showed dilated Bowman's space, inflammatory cell infiltration, glomerular and peritubular vascular congestion and swelling of renal tubular epithelial cells. Erboga M et al [18] showed prominent degenerative changes with tubular degeneration, tubular dilatation, tubular cell swelling, cellular vacuolization, glomerular congestion and degeneration in the renal cortical tissues.…”
Section: Discussionsupporting
confidence: 93%
“…Anticancer activity of SL was also reported against several cancer types [1]. Some studies reported that SL suppresses caspase activation [9] and prevents apoptotic cell development [2,24]. Our results suggested that pre-treatment of high dose (200 mg/kg/day) of SL was significantly reduced caspase activities against VA-induced hepatotoxicity and concentration of SL is important for balancing oxidant-antioxidant status in liver tissues.…”
Section: Discussionsupporting
confidence: 70%
“…SL has been widely used for the treatment of liver and gall bladder disorders, and also has beneficial effects on different organ illnesses and broad range of cancers [8]. Hepatoprotective [3], anti-apoptotic, strong antioxidant [8], anti-inflammatory, immunomodulatory [8,9], membrane-stabilizing [7], and antiviral properties [9,10] of SL have been reported in previous studies. Experimental and clinical studies also indicated that antioxidant activity of SL reduces inflammatory reaction, promotes hepatocyte regeneration, and inhibits fibrogenesis [7].…”
mentioning
confidence: 80%